Bersama Wujudkan Lingkungan Bersih dan Indah di Desa Hutanamra melalui Kegiatan Gotong Royong - Imelda Sihombing; Aryati Ops; Yolanda Panjaitan; Maria Silaban; Nadya Sianturi; Debora Dongoran; Santa Tamba; Putri Pasaribu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to create a clean and beautiful environment in Hutanamora Village through gotong royong activities, which increase the value of togetherness and care for the environment. The research used a participatory approach that actively involved the village community in the planning, implementation and evaluation of events. Environmental cleaning, waste management, and greening of the village's strategic areas were the focus of the gotong royong program. The results showed that gotong royong not only improved the cleanliness and beauty of the environment but also increased the sense of unity and cooperation among residents. In addition, the community is increasingly aware of the importance of protecting the environment. So, gotong royong is a great solution to make the environment clean and beautiful. It also builds the character of a community that cares and is responsible for environmental sustainability.